EFFECT OF AGE AND GENDER ON ACUTE COPPLICATIONS OF HEMODIALYSIS IN PATIENTS WITH CHRONIC KIDNEY DISEASE SECONDARY TO DIABETES MELLITUS - Bilal, Ahmad; Zaman, Fakhar Uz; Abrar, Syed Muhammad; Rahim, Sheema; Hussain, Mohammad Adil; Shah, Sajid Ali (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the effect of age and gender on acute complications of hemodialysis in patients with chronic kidney disease (CKD) secondary to diabetes mellitus. Study Design: Cross-sectional study. Place and Duration of Study: Department of Medicine, Ayub Teaching Hospital Abbottabad, from Jan 2015 to Oct 2016. Methodology: Only patients who were diagnosed cases of diabetes for the last 10 years, and were aged between 30 and 65 years were included in the study. Any patient who was suspected to have chronic kidney disease due to any other cause e.g. glomerulonephritis, Polycystic Kidney Disease, analgesic abuse, atherosclerosis, Obstructive nephropathy and chronic hypertension were excluded to control confounding and bias. Results: Out of these 202 patients, 92 patients (45.54%) patients developed acute complications of hemodialysis. Hypotension was the commonest complication followed by atrial fibrillation, fever and headache. When the acute complications of hemodialysis were stratified according to sex, age and duration of chronic kidney disease, the results were statistically not significant (p 0.28, 0.34 & 0.085 respectively). Conclusion: This study showed that hypotension is the most common acute complication of hemodialysis followed by atrial fibrillation and fever. The effect of age and gender on acute complications of hemodialysis was statistically insignificant.